2019
DOI: 10.1002/ange.201812880
|View full text |Cite
|
Sign up to set email alerts
|

Kinetische Studie zu Donor‐Akzeptor‐Cyclopropanen: Strukturelle und elektronische Einflüsse auf die Reaktivität

Abstract: Die Kinetik einer (3+ +2)-Cycloadditionsreaktion von 18 unterschiedlichen Donor-Akzeptor-Cyclopropanen mit einem Aldehyd wurde mittels NMR-Spektroskopie untersucht. Eine hçhere Elektronendichte des Donorsubstituenten führt zu einer 50-fachen Beschleunigung der Reaktion im Vergleich zum nativen System (Donorsubstituent = Phenyl), wohingegen ein elektronenziehender Substituent die Reaktion um den Faktor 660 verlangsamt. Dieses Verhalten korreliert mit dem Hammett-Parameter s.D ie erhaltenen Geschwindigkeitskonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 122 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Variation of substituents in SnCl 4 ‐catalyzed (3+2)‐cycloadditions of 2‐aryl‐1,1‐di(alkoxycarbonyl)cyclopropanes with p ‐fluorobenzaldehyde recently studied by the Werz group resulted in a linear Hammett relationship, in which EDG‐substituted substrates reacted faster than EWG‐substituted analogues. [16a] Accordingly, Werz reported that relaxed force constants calculated for the C1−C2 bonds, which undergo cleavage in the course of the reactions, correlated with the relative reaction rates: lower force constants for EDG‐substituted cyclopropanes were associated with faster reactions. We assume that complexation with the Lewis acid SnCl 4 enhanced the electron‐deficiency of the 1,1‐di(alkoxycarbonyl)‐substituted cyclopropanes such that their reactivity was entirely governed by the degree of the C−C bond polarization, consistent with the intimate ion pair mechanism suggested for this reaction by Johnson and coworkers.…”
Section: Resultsmentioning
confidence: 99%
“…Variation of substituents in SnCl 4 ‐catalyzed (3+2)‐cycloadditions of 2‐aryl‐1,1‐di(alkoxycarbonyl)cyclopropanes with p ‐fluorobenzaldehyde recently studied by the Werz group resulted in a linear Hammett relationship, in which EDG‐substituted substrates reacted faster than EWG‐substituted analogues. [16a] Accordingly, Werz reported that relaxed force constants calculated for the C1−C2 bonds, which undergo cleavage in the course of the reactions, correlated with the relative reaction rates: lower force constants for EDG‐substituted cyclopropanes were associated with faster reactions. We assume that complexation with the Lewis acid SnCl 4 enhanced the electron‐deficiency of the 1,1‐di(alkoxycarbonyl)‐substituted cyclopropanes such that their reactivity was entirely governed by the degree of the C−C bond polarization, consistent with the intimate ion pair mechanism suggested for this reaction by Johnson and coworkers.…”
Section: Resultsmentioning
confidence: 99%